A Neo-Classical Theorem - Robinson, Joan (Review of Economic Studies, 1962)
Journal Article A Neo-Classical Theorem Get access Joan Robinson Joan Robinson Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 3, June 1962, Pages 219–226, https://doi.org/10.2307/2295956 Published: 01 June 1962